Pengetahuan Tradisional Masyarakat Suku Nyalik tentang Ubi Jalar [Ipomoea batatas (L.) Lam.] di Distrik Silimo, Kabupaten Yahukimo Papua - Kalep Segenil; Linus Y. Chrystomo; Maklon Warpur (Jurnal Biologi Papua, 2017)
Nyalik tribe community in Silimo District Yahukimo Regency Papua have traditional knowledge about the sweet potato (Ipomoea batatas (L.) Lam.) applied it in the cultivation. Traditional knowledge is knowledge of local community in an area that a culture tradition handed down from generation to generation. Traditional knowledge about the sweet potato is a wealth of local wisdom in Papua, which need to be investigated, developeds, utilized and conserved the types of sweet potatoes which is quite much and widely spread in Papua. It is important to support local food diversification program and to improve national food security. The method of the research is descriptive qualitative method by doing observation. Data was obtained from the original source of the sweet potato farmer as respondent by using questionnaire and also measurement and documentation in the field. The result showed that Nyalik tribe people have recognized, identified and cultivated 33 types of sweet potatoes and grouped them according to their used into 5 groups: as for baby food or children, adult food, sick person, traditional ceremonies and animal feed. Nyalik tribe community has a traditional knowledge about the sweet potato and cultivation system and also how to overcome the obstacles in sweet potato cultivation. Keywords: Traditional knowledge, I. batatas, Nyalik tribe, Silimo, Yahukimo